Use of Positive Strengthening Methods Inferential Reinforcement of Low Rates (DRL) in Reducing Impulsive Behavior for ADHD Children - Rilva Afrilia; Toni Yudha Pratama; Reza Febri Abadi; Yuni Tanjung Utami (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2021)
The goal of the study was to determine the use of diferential reinforcement of low rates (DRL) positive strengthening methods to reduce verbal impulsive behavior in ADHD (Attention Deficit Hyperactivity Disorder)children. Quantitative research method experiments Single Subject Research (SSR) with design A-B-A. Thesubject in this study was 1 (one) ADHD student in the 12th grade of SKh Bina Citra Anak Serang High School, Banten. Data collection uses observation techniques performed during the prior, administration of interventions, and after the intervention. This study was conducted in the school for 15 observations conducted in three phases, namely 5 baseline sessions before the intervention (A1), 6 sessions in the intervention phase (B), and 4 sessions in the baseline phase (A2). In this study, a reduction in the rate of verbal impulsive behavior cut off the speech of others after the use of the DRL method from the previous results of the average score of the appearance of verbal impulsive behavior that is 1 time / minute reduced to 0.6 times / minute.